Cartographier Fort-de-France à partir de sources historiques et littéraires : pour une géohistoire postcoloniale - Juliette Morel (Humanités Numériques)
At a time when information systems for geographic and historical reconstruction based on the digitization of cartographic and scientific archives proliferate, it is necessary to develop methods for the study of formerly colonized spaces. These spaces raise specific problems in the treatment of sources and the modelling process : they require a geomatic perspective which has to be critical, delicate, and even paradoxical. Interdisciplinary experiments carried out in the still nascent field of spatialized digital humanities offer leads for responding to the apparent paradox of geomatics in postcolonial and decolonial contexts. This article aims at demonstrating the relevance of such methodological hypotheses by developing the example of the city of Fort-de-France in Martinique. The purpose of this paper is to illustrate that the integration of alternative geohistorical information, such as that derived from novels, enriches the geographic and historical modelling of the city. Our intention is to open a critical research project based on the enrichment of geographic information by the digital humanities, to show its relevance and legitimacy and to raise the questions that appear in such work.